Health-related quality of life in children with autism spectrum disorders and children with developmental language disorders. (May 2019) - Coales, Catherine; Heaney, Natalie; Ricketts, Jessie; Dockrell, Julie E; Lindsay, Geoff; Palikara, Olympia; Charman, Tony
Background and aims: There is a paucity of literature investigating health-related quality of life in neurodevelopmental populations including children with developmental language disorders and children with autism spectrum disorder. Health-related quality of life in these two groups remains poorly understood. Furthermore, studies have typically relied on reports from caregivers and teachers rather than using self-report measures. The aim of the current study is to compare the levels and profiles of self-reported health-related quality of life of children with developmental language disorders and children with autism spectrum disorder. Methods: Participants comprised 114 7-to-13-year-old children with developmental language disorders ( n  = 63) and children with autism spectrum disorder ( n  = 51) attending mainstream school. Self-reported health-related quality of life was measured using the KIDSCREEN-52. We also collected standardised measures of receptive language, autism spectrum disorder symptoms, nonverbal IQ and emotional and behavioural problems. Results: Children with developmental language disorders reported health-related quality of life commensurate with normative ranges, except for 2 of the 10 dimensions; the Moods and Emotions domain and the Social acceptance/bullying domain, which were below norms. Children with autism spectrum disorder reported significantly lower health-related quality of life compared to norms and the developmental language disorders group. However, when the effects of non-verbal ability and language – on which the groups were not matched – were covaried most group differences fell to non-significance or disappeared. Child characteristics showed few associations with dimensions of health-related quality of life across groups. Conclusions: Children with autism spectrum disorder may be particularly vulnerable to poorer health-related quality of life and the relevant professionals need to be aware of this. Children with developmental language disorders exhibit a profile of health-related quality of life more in-line with average ranges. However, certain domains warrant monitoring and may benefit from intervention. Many of the between-group differences in self-reported health-related quality of life disappeared when non-verbal and language ability were covaried, though neither of the covariates was systematically related to scores. Other within-child factors such as emotional understanding and competence should be explored in future studies. Implications: Further research into child and contextual factors may elucidate risk or protective factors for health-related quality of life in children with neurodevelopmental disorders.